How Does Lower-Body and Upper-Body Strength Relate to Maximum Split Jerk Performance? - Soriano, M. A.; Jiménez-Ormeño, E.; Amaro-Gahete, F. J.; Haff, G. G.; Comfort, P. (The Journal of Strength and Conditioning Research, 2022)
The aims of this study were to (I) determine the relationships between the maximum dynamic strength of the upper and lower body, measured by overhead press and back squat 1 repetition maximum (1RM) performances, and the split jerk (SJ) performance in trained weightlifters and (II) explore the magnitude of these relationships for men and women to establish sex-specific prediction equations. Twenty men (age: 28.9 ± 6.6 years; height: 1.8 ± 0.1 m; body mass [BM]: 82.5 ± 10.2 kg; weightlifting training experience: 4.2 ± 2.4 years) and 13 women (age: 27.7 ± 4.4 years; height: 1.7 ± 0.1 m; BM: 61.8 ± 5.2 kg; weightlifting training experience: 2.7 ± 1.7 years) competitive weightlifters participated. The 1RM performances of the overhead press, back squat, and SJ were assessed for all subjects. A very strong correlation exists between the back squat and overhead press, with maximum SJ performance for all subjects (r = 0.97; p < 0.001). Similarly, very strong correlations were found for men (r = 0.90, p < 0.001) and women (r = 0.90, p = 0.0002), separately. The coefficient of determination indicates that the prediction equation for the maximum SJ performance is quite accurate (R2 = 0.94) for all subjects and men (R2 = 0.83) and women (R2 = 0.81), separately. These results provide evidence that the maximum strength of the upper and lower body are major contributors to SJ performance. In addition, SJ performance can accurately be predicted from the back squat and overhead press performances.